Eksplorasi Etnomatematika pada Alat Musik Kecapi Siter - Soedarbe, Yorian; Arreza, Dimas; Adriantoro, Albertus Argo (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Culture, especially musical instruments, is what students are most interested in because it is easy to understand and understand, in contrast to mathematics, which is less attractive to students because the knowledge is abstract. This makes students have difficulty understanding the material in school. Ethnomatematics is a solution that can be presented to deal with this problem. This study aims to combine elements of culture and mathematics which are expected to facilitate the student learning process. The research data were obtained by means of interviews and documentation from the owner of the Kecapi Siter musical instrument. The results of Kecapi Siter's research show that there are geometric concepts, arithmetic sequences and trigonometry. Existing research results can be used as a reference for educators for learning in the classroom.